Mediating effect of psychological safety climate in the relationship between psychological factors and individual safety performance in the Malaysian manufacturing small enterprises - Rahlin, Nor Azma; Abdul Majid, Abdul Halim; Mustafa, Munauwar (International Academic Research Journal, 2016)
SME is a backbone of Malaysian economic development, however high number of occupational accident and injuries are major financial issues. Many meta-analysis of the safety climate and safety performance consistently indicated that associate with the reduction in the number of accident occurrence in the organization.Therefore, the purpose of this study is to explore the mediating effects of on psychological safety climate in the relationship between psychological factors and individual safety performance in the Malaysian manufacturing small enterprise. Quantitative research using self-administrative questionnaires have been conducted on 377 employees from 11 small manufacturing enterprise firms based on stratified random sampling. The response rate was at 65 % from 240 returned questionnaires.The results of a preliminary validation showed that the scale is a reliable and valid instrument to measure the essential elements of psychological safety climate for Malaysian manufacturing small enterprise.The result confirmed that here were strong positive correlations between psychological safety climate and individual safety performance. As predicted, psychological safety climate found to be directly influenced by psychological factor but psychological factor not directly correlated with individual safety performance.Besides that, the findings of this study revealed that psychological safety climate significantly mediated the relationship between psychological factor and individual safety performance.Finally, the implications and suggestions for future studies and practice are discussed.